The current spectrum of infections in cancer patients with chemotherapy related neutropenia - Ashfaq, Maliha; Haider, Ghulam; Ather, Tooba; Ahsan, Mahnoor; Khan, Mohammad Ejaz; Seher, Sana (Infectious Diseases Journal of Pakistan, 2023)
Background: New cancer treatments have improved patient survival but also bring side effects like weakened immunity and higher infection risk. The present study aimed to assess the pattern of blood stream infections and antimicrobial resistance in blood isolates of neutropenic patients. Material and Methods: This Cross-sectional, observational study was conducted at Department of Oncology, Jinnah Postgraduate Medical Centre, Karachi, Pakistan between August 2019 to August 2020. Malignant patients who underwent chemotherapy and presented with fever, neutropenia, and positive bacterial blood culture were enrolled in the study. Patients with a recent history of blood transfusion were excluded. The spectrum of bacterial infections and the antimicrobial resistance patterns of causative organisms isolated from blood were studied. The CLSI standard antimicrobial panel was used for each microorganism. Findings were presented in tabular form. Results: During the study period 95 organisms were isolated from the blood cultures. Strains of E. Coli, Klebsiella, Pseudomonas, S. Aureus, S. Pneumoniae, were found in 27 (28.4%), 18 (18.9%), 13 (13.7%), 17 (17.9%), and 2 (2.1%) patients, respectively. 44.0% of E. coli, 68.8% of Klebsiella, and 38.5% of Pseudomonas were resistant to tazobactam. 92.6% of E. coli, 88.2% of Klebsiella, 100% of Pseudomonas were resistant to Co-amoxiclav. 52.9% of Staph aureus were resistant to methicillin. 23 (92.0%) strains of E. coli, 15 (83.3%) strains of Klebsiella, 6 (46.2%) strains of Pseudomonas, and 11 (68.8%) of Staph aureus were resistant to ciprofloxacin. Conclusion: Resistance to the majority of the commonly used antimicrobial drugs was noted. Continuous antimicrobial resistance surveillance of the everchanging spectrum of causative organisms and their characterization is very important to treat the bloodstream infections (BSI) in cancer patients with chemotherapy induced neutropenia. Keywords: Neutropenia Infection, Fever, Antimicrobial resistance, Chemotherapy.